2020
DOI: 10.9734/ajeba/2020/v16i430244
|View full text |Cite
|
Sign up to set email alerts
|

Food Prices and the Challenge of Food Security in Bayelsa State, Nigeria

Abstract: High food prices are seen as synonymous with food insecurity. This is because it defiles one of the four cardinals of food security; food accessibility. To ensure the attainment of food security which is a common denominator in the United Nation’s MDGs and SDG as eradication of hunger, food must be economically accessible by all and sundry. Bayelsa State has been bedevilled by exorbitant food prices as confirmed by NBS data released in March 2020 which placed the state as having the highest cost in 15 out of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…A majority of the farmers were still in their middle and actively productive years. The result agrees with studies (Anugwa and Agwu, 2018; Ochuba and Cookey, 2020) that have documented that women in Bayelsa State are more involved in food crop farming, processing and marketing of artisanal fisheries than their male counterparts; noting that historically, Ijaw men are not farmers by nature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A majority of the farmers were still in their middle and actively productive years. The result agrees with studies (Anugwa and Agwu, 2018; Ochuba and Cookey, 2020) that have documented that women in Bayelsa State are more involved in food crop farming, processing and marketing of artisanal fisheries than their male counterparts; noting that historically, Ijaw men are not farmers by nature.…”
Section: Discussionsupporting
confidence: 90%
“…The farmers’ experience of both flooding and drought highlights the extremes of weather events that are consequences of climate change (Weber, 2010). As noted by Ochuba and Cookey (2020), the most common natural/climate change-related disaster in Nigeria coastal communities is flooding (Ochuba and Cookey, 2020). However, at the time of conducting this study, farmers indicated high temperatures and drought as severe climate change consequences being experienced presently, and for them, this was a dilemma as they have been most challenged by flooding up till the last production season and have had to change their planting times, but now, the rains have not come as expected.…”
Section: Discussionmentioning
confidence: 99%